Solvent-Free 1,3-Dipolar Cycloadditions of Nitrones for a More Sustainable Synthesis of Glycomimetics - Debora Pratesi; Alessio Morano; Andrea Goti; Francesca Cardona; Camilla Matassini (Reactions)
1,3-Dipolar cycloadditions on nitrone dipoles are key reactions to access five-membered heterocycles, which are useful intermediates in the synthesis of biologically relevant glycomimetics. The good atomic balance and high stereoselectivity characteristic of such reactions make them good candidates for the development of green protocols. In the present work, these features were maximized by avoiding the use of organic solvents and considering starting materials derived from biomass. Reactions involving (acyclic and cyclic) carbohydrate-derived nitrones as dipoles and levoglucosenone as dipolarophile were considered. Performing selected 1,3-dipolar cycloadditions in neat conditions showed reduced reaction times, maintaining similar selectivity and yields with respect to the classical protocols. The use of microwave irradiation and orbital shaking were also exploited to increase the sustainability of the synthetic protocols. The collected results highlight the potential of solvent-free 1,3-dipolar cycloadditions in the design of efficient synthetic routes according to green chemistry principles, such as prevention, atom economy, safer solvents and auxiliaries, and use of renewable feedstocks.